A novel approach for quantitative imaging of the seated anatomy of the buttocks using ultrasound and MRI - Mogale, Nkhensani; Scott, Justin D.; Schanz, Daniel; Ilyasov, Viktor; Bush, Tamara Reid; van Schoor, Albert-Neels; Slade, Jill M. (Frontiers in Physics, 2023)
Background: Pressure injuries are commonly noted in individuals who use wheelchairs for mobility and sit for prolonged periods. Understanding soft tissue composition is an essential part of treating and preventing pressure injuries. This study proposes novel approaches to imaging soft tissue of the buttocks in unloaded and loaded conditions using ultrasound (US) and magnetic resonance imaging (MRI). Methods: The soft tissue of the buttocks was measured in able-bodied participants (n = 26, 50% female) and 1 male with a spinal cord injury using an innovative chair that allowed seated US acquisition of the buttocks and a newly developed MRI compatible loader. US test-retest reliability (reproducibility) of buttocks soft tissue was assessed, and US was validated with MRI. Soft tissue was measured between the peak of the ischial tuberosity (IT), proximal femur and the skin. MRI was used to quantify fat fraction of the gluteus maximus muscle with the goal of determining the influence of intramuscular fat on loaded soft tissue responses and was used to assess tissue thickness during buttocks loading. Results: US reproducibility was excellent, ICC = 0.934 - 0.981, with no statistical differences between scan days. Coefficients of variation (CVs) between visits ranged from 2.5% - 7.4% for loaded and unloaded tissue. US and MRI measures of tissue thickness were significantly correlated (r = 0.68 - 0.91, p ≤ 0.001). US underestimated unloaded tissue thicknesses with a mean bias of 0.39 - 0.56 cm. When the buttocks were loaded, US and MRI total tissue thickness was reduced by 64.2 ± 9.1% (p < 0.001). The US and MRI total unloaded total soft tissue of the IT was correlated with loaded tissue thickness (r = 0.54 - 0.67, p ≤ 0.027). Intramuscular fat of the gluteus maximus was not correlated to changes in muscle thickness with loading (r = 0.05, p > 0.05). Conclusion: We have developed and validated novel US methodology using MRI as a comparison to investigate soft tissue anatomy and deformation during sitting and loading. This data acquisition in the loaded condition is unique and fills an unmet need in understanding loading and pressure injury formation.